Al2(SO4)3 alters the antioxidant mitochondrial metabolism of Botritys cinerea and optimizes the production of cellulose and oxidative degrading enzymes (Research, Society and Development, 2023)
The enzymes produced by pathogenic fungi, especially Botritys cinerea, deserve specific attention due to the diversity of their applications, mainly in biofuel production, food processing, and the pharmaceutical industry. Thus, this work used Al2(SO4)3 as a stressor in order to evaluate if the stress levels caused by the concentrations of 100, 250, 500, and 1000 ppm were sufficient to increase the production of hydrolytic cellulolytic enzymes (FPase, CMCase, Avicelase, β-glucosidase, xylanase) and oxidative (laccase and manganese peroxidase). The study also evaluated the stress levels in previously treated mycelia of B. cinerea and whether they corresponded to the different states of mitochondrial respiration. Our study indicates that Al2(SO4)3 increased the production of cellulolytic and oxidative enzymes in all concentrations in a dose-dependent manner and that Al2(SO4)3 alters the mitochondrial respiratory rate, with lower ATP productions, indicating that less-coupled mitochondria were obtained and that this may be due to the increase of oxidative stress. Thus, it is plausible to suggest the use of Al2(SO4)3 in the production of cellulolytic enzymes, which could be used in the hydrolysis stage of second-generation ethanol production processes, as it reduces the time required for enzymatic expression applications in industrial processes.